Strategi Asesmen Guru Dalam Mengembangkan Aspek Motorik Siswa Dalam Pembelajaran - Milda Novianti; Iis Komariah (Yayasan Al-Afif, 2026)
Dance learning in elementary schools helps students develop aesthetic expression and gross and fine motor skills. Appropriate evaluation is essential during this learning process. This evaluation is crucial for teachers to accurately and continuously track student progress. Therefore, this study aims to examine how teachers use assessment strategies in dance learning in fifth-grade students at Garut Islamic School Prima Insani Elementary School. This study examines these assessment strategies, particularly those related to student motor development. The objectives of this study are to identify assessment strategies used by teachers to improve students' motor skills, assess whether students' motor skills have improved during dance learning, and explain the difficulties teachers face when using these assessment strategies. The focus of this study is on the use of formative assessment during the learning process, not at the final evaluation stage. This study uses a descriptive qualitative methodology, collecting data through observation, in-depth interviews, and documentation. The research subjects consisted of dance teachers, the principal, and fifth-grade students. Data were analyzed thematically to identify patterns of assessment strategies and the impact of dance learning on students' motor development. The results of the study indicate that teachers used formative and diagnostic assessment strategies with a differential approach and direct observation. Rubrics were used to assess motor coordination, flexibility, rhythm, and manual dexterity. The motor skills of most students were categorized from